2020
DOI: 10.37464/2020.373.120
|View full text |Cite
|
Sign up to set email alerts
|

A national survey of nurses who care for people with intellectual and developmental disability

Abstract: Objective: To describe the roles that Australian nurses play, the breadth of skills that they deploy, and the range of contexts in which they practice. Study design and methods: This cross-sectional study used a descriptive survey where data were collected online using Qualtrics©. Survey respondents were nurses whose primary role was caring for people with intellectual and developmental disability. In addition to demographic data, the main outcome measures were: nursing roles, practice and context. Results: Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Finally, our findings have implications for research, education and practice. For example, Sweden would benefit immensely from following the more recent Australian initiatives within the field of nursing and IDD, that is, by conducting a national mapping study of the educational opportunities within the field of IDD (Furst & Salvador‐Carulla, 2019; Trollor et al., 2016) and performing a national survey (Wilson et al., 2020) to explore how many RNs work in services caring for people with IDD, in what settings they work and their roles in care. As with many other countries, Sweden has a national register for newly qualified nurses; however, how many of those going on to work within the field of IDD are unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, our findings have implications for research, education and practice. For example, Sweden would benefit immensely from following the more recent Australian initiatives within the field of nursing and IDD, that is, by conducting a national mapping study of the educational opportunities within the field of IDD (Furst & Salvador‐Carulla, 2019; Trollor et al., 2016) and performing a national survey (Wilson et al., 2020) to explore how many RNs work in services caring for people with IDD, in what settings they work and their roles in care. As with many other countries, Sweden has a national register for newly qualified nurses; however, how many of those going on to work within the field of IDD are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…This shift has had consequences for them, for the role of nursing and for the delivery of care. A recent cross‐sectional study found that Australian RNs had a variety of roles and engaged in a considerable range of practices related to the needs of patients with IDD (Wilson et al., 2020). Rather than the delivery of care in institutional settings, in many countries, community care has now been designated as the main provider of healthcare to patients with IDD.…”
Section: Introductionmentioning
confidence: 99%
“…Given that intellectual disability operates on the fringes of the nursing profession and that the size of the specialty of intellectual disability nursing accounts for just 6.75% of the nursing profession [97] there is a need for national leadership from within the profession, health service providers and health agency. Given the evidence of the complex health needs, access issues and health disparities of people with intellectual disability it is essential that we recruit and retain nurses with specialised unique knowledge and skills, and competence to work with people with intellectual disability [98][99][100].…”
Section: Discussionmentioning
confidence: 99%
“…The paraphrased progress notes and nonparticipant observation fieldnotes offer a glimpse into the specialised care and management of Derek when his health deteriorates rapidly and seriously. However, they do not fully capture the cycle of observation, assessment, intervention and outcome evaluation that underpins clinical decision making central to the work that RNs perform [28], nor the broad spectrum of tasks undertaken and knowledge and skills applied by RNs caring for people such as Derek on a shift-by-shift basis [12]. Caring for Derek, and people with similar diagnoses and support needs, requires detailed knowledge of human body systems and the interactions between them, pathophysiological pathways and the ways that chronic illness/es can cascade rapidly during an acute exacerbation, the action and interaction of multiple pharmacological agents, and critical insight into the nursing interventions and clinical decision making needed.…”
Section: Discussionmentioning
confidence: 99%
“…We argue that there is at least one quality alternative to the current models of care delivery, in particular for people with intellectual disability and multiple chronic and complex health problems, and this is a registered nurse-led model of relationship centred care [10], that is not only highly technical, but also uniquely relational in its approach [11]. However, this alternative remains one that while still in practice across some contexts [12], has never been compared to a model of care absent registered nurses (RNs) in terms of financial cost.…”
Section: Introductionmentioning
confidence: 98%